EDUKASI GIZI WANITA PEKERJA SEBAGAI UPAYA PENCEGAHAN STUNTING - Andriani, Eka; Nurdiana, Astri (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Devotion community aims to bring working woman about the importance of education in preventing balanced nutrition supported by stunting company PT.Changsin in Karawang. Methods used in this activity is education with information directly to women aged 50 workers fertile, we do the pre and post test having given intervention information about nutrition balanced and stunting. Of the activities is the increased knowledge and attitudes about 45 % respondents. It is beneficial and in line with government efforts in preventing stunting in Karawang